Development of an integrated bean root rot control strategy for Western Kenya - Otsyina, R.M.; Ajanga, SI; Buruchara, Robin Arani; Wortmann, Charles S. (1998)
Root rot severely constrains bean (Phaseolus vulgaris L.) production in parts of Western Kenya. Genetic and soil management options were evaluated for an integrated root rot management approach. Four hundred genotypes were progressively screened in the field for resistance to root not over six seasons. A sequence of problem-solving trials on cultural methods was conducted over four seasons. All trials were conducted in root rot infested fields of farmers. No resistant varieties were found in the Kenyan germplasm collection of 374 accessions. Ten resistant varieties were identified from 26 introductions which were known to be resistant to root rots in Rwanda. Farmers preferred MLB-49-89a because of its early maturity, SCAM 80-CM/5 and RWR 532 because of their high yield and seed type, and the late maturing RWR 719 as it was seen as a replacement for a previously popular cultivar which succumbed to root rots. Crop tolerance to root rots was greatly improved by improving soil fertility through application of diammonium phosphate or certain organic manures, and less so by sowing on ridges. Application of several rapidly decomposing green manures, including Tithonia diversifolia which was abundantly available in field borders, resulted in improved crop tolerance to root rot.